On Securing a Door with Finger Print Biometric Technique - Olabode Afolabi, Adeolu; Alice, Oke (Transactions on Engineering and Computing Sciences, 2014)
Security of valuables is as paramount as their acquisition. Valuables ranging from human lives to expensive resources and sensitive data need to be tightly secured. In this present day when armed robbery has gotten more sophisticated particularly in developing countries, there is the need for tighter security means, and one of the most secured technologies that can be employed is biometrics, finger print door lock to be precise. Biometrics is the science and technology of measuring and analysing biological data, biometrics measures and analyses human body characteristics such as DNA, fingerprint, eye retina and iris, voice pattern, facial pattern and hand measurement [1]. The software that drives the microcontroller was done using the C language on MPLAB compiler, the coding was segmented into various modules; first, the module that drives the LCD screen, next is the module that drives the finger print scanner, this instructs the scanner to first register users and allow the inputted finger print to be compared with the pre-registered finger prints. The pre-registered finger prints are saved on the IC registers of the Micro controller. An alert is sounded whenever a fingerprint that is not found in the Microcontroller memory is placed on the scanner as an intruder. The construction of this project was done in three different stages, the writing of the code (driver) which controls the Microcontroller using C language, the implementation of the whole project on a solder-less experiment board, the soldering of the circuits on Vero-boards and the coupling of the entire project to the casing. The implementation of this project was done on the breadboard as a prototype, the power supply was first derived from a bench power supply in the electronics laboratory, in all the development guaranteed security for illegal intrusion of illegal entity to room, the mechanism can be implemented in a broader sense on a door where a there is restriction of access.